Measurement of the branching fractions of the radiative leptonic [tau] decays [tau] → e[gamma ny ny] and [tau] → [mu gamma ny ny] at BABAR - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We perform a measurement of the τ→lγν¯ν (l=e,μ) branching fractions for a minimum photon energy of 10 MeV in the τ rest frame, using 431 fb−1 of e+e− collisions collected at the center-of-mass energy of the Υ(4S) resonance with the BABAR detector at the PEP-II storage rings. We find B(τ→μγν¯ν)=(3.69±0.03±0.10)×10−3 and B(τ→eγν¯ν)=(1.847±0.015±0.052)×10−2, where the first quoted error is statistical and the second is systematic. These results are substantially more precise than previous measurements.
Im Titel erscheinen die folgenden Zeichen in griechischer Schrift: tau, gamma, mu, ny. Das jeweils zweite ny erscheint mit einem Querbalken
Gesehen am 16.06.2020